An experience of jungian group psychotherapeutic assistance, with an emphasis in the corporal dimension, in the context of brazilian public health system - Greger Tavares, Sandra Maria (O Mundo da Saúde, 2010)
This study investigated the relevance of using a modality of Jungian group psychotherapy according to Sándor’s body organismic method, in view of the demand for mental health presented by users of a Basic Health Unity of SUS – the Brazilian Unified Health System. Tree open psychotherapy groups were composed having seven adult patients and observed for a year. The qualitative analysis of results based on the comparison between the dynamics of these three groups, confronting the points of convergence between them. We concluded that this kind of psychotherapy made possible a greater opening and adhesion to the psychotherapeutic process, with the establishment of very solid bonds of confidence. The following psychosocial transformations were observed in the period of a year: a greater definition and integration of the physical image of subjects and groups; a reduction or elimination of initial physical symptoms; modifications as for the form of thinking about the social-economic conditions and how to act in this context; a greater opening to social contact and to physical interaction by patients, as well as a recovering of subjects work capacity and creative potential.